Strategy, Evolution, and War : From Apes to Artificial Intelligence - Payne, Kenneth, 1974- (Book collections on Project MUSE., 2018)
This book is about the psychological and biological bases of strategy making in war as they have evolved in humans over our history as a species. The book is also a cautionary preview of how Artificial Intelligence (AI) will revolutionize strategy more than any development in the last three thousand years of military history. Machines will make important decisions about war on both sides, and they may do so without input from humans. Kenneth Payne describes strategy as an evolved package of conscious and unconscious behaviors with roots in our primate ancestry. Human-made strategy is influenced by emotion as well as reason, with both positive and negative results. The strategic implications of AI are profound because they depart radically from the biological basis of human intelligence. Rather than being just another tool of war, AI will exponentially speed up decisionmaking, make choices humans might not make, and force faster actions and reactions. This book is a fascinating examination of the psychology of strategy-making from prehistoric times, through the ancient world, and into the modern age. It also offers a concerning preview of a future when humans cede at least some control over their destiny.